Monitoring Kualitas Udara dan Kontrol Air Purifier Honeywell HHT-080 - Yogi Syaputra; Noptin Harpawi; Yuli Triyani; Wahyuni Khabzli (Politeknik Caltex Riau, 2022)
Air is very important for the survival of living things, air quality will affect the state of human health. At present air quality is only monitored by KLH (Ministry of Environment) of Riau Province, with monitoring points only 1-3 points per city / regency in Riau. The frequent occurrence of forest fires in Riau, causing air quality to deteriorate rapidly so it requires a tool that can monitor air quality and improve air quality to maintain human health. Therefore, the authors conducted research and design of tools to be able to monitor air quality (CO gas levels) and improve air quality in the room. The workings of this monitoring device are MQ-7 gas sensors measuring CO (carbon monoxide) gas levels, where the data is then processed and sent through a wi-fi network using ESP8266 and the data is also used as a reference for control the air purifier in the room. The results of this monitoring are shared using Google Spreadsheets by e-mail to the people whom concerned. The MQ-7 sensor works best in the range of 50-150 ppm carbon monoxide gas with a deviation of 14 ppm from a calibrated multi gas detector. Keywords: Monitoring, Gas CO, ESP8266, MQ-7, Google Sheets, Air quality, Air Purifier.